2008
DOI: 10.1039/b802165a
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multi-unit electrophysiology and plastic culture dishes for network neuroscience

Abstract: The electrophysiological characterisation of cultured neurons is of paramount importance for drug discovery, safety pharmacology and basic research in the neurosciences. Technologies offering low cost, low technical complexity and potential for scalability towards high-throughput electrophysiology on in vitro neurons would be advantageous, in particular for screening purposes. Here we describe a plastic culture substrate supporting low-complexity multi-unit loose-patch recording and stimulation of developing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…In 2009, Dworak and Wheeler [8] analyzed the relationship between signal amplitudes and electrode impedances and suggested that signals in microtunnels could be as large as 2.4 mV as measured between an electrode placed within the tunnel and a distant reference electrode that is bathed in media electrically coupled to the wells on either side of the tunnels. The Claverol-Tinturé lab reported large signals (up to 8 mV for a 2 × 6 μm tunnel) recorded differentially from two otherwise isolated wells connected by a tunnel within which axons grew and propagated signals [14], [15]. This group further reported signals from electrodes within the tunnel (referenced to a well) of up to 1.5 mV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Dworak and Wheeler [8] analyzed the relationship between signal amplitudes and electrode impedances and suggested that signals in microtunnels could be as large as 2.4 mV as measured between an electrode placed within the tunnel and a distant reference electrode that is bathed in media electrically coupled to the wells on either side of the tunnels. The Claverol-Tinturé lab reported large signals (up to 8 mV for a 2 × 6 μm tunnel) recorded differentially from two otherwise isolated wells connected by a tunnel within which axons grew and propagated signals [14], [15]. This group further reported signals from electrodes within the tunnel (referenced to a well) of up to 1.5 mV.…”
Section: Introductionmentioning
confidence: 99%
“…Here we expand upon the range of potential tunnel dimensions where this effect can be seen with conventionally sized microtunnels (3 μm × 10 μm, most commonly reported and commercially available) and commercially available microelectrode arrays (most commonly with 30 um diameter electrodes), beyond the specially fabricated electrodes designed to intersect the wells reported previously [8], [14], [15]. Further, we report amplitudes (as large as 4.5 mV) that often exceed what has been previously reported for electrodes in tunnels, with correspondingly large signal to noise ratios (up to 450).…”
Section: Introductionmentioning
confidence: 99%
“…This builds on in vitro studies that have described neurite growth into enclosed microchannels, as well as on previous reports on the recording of neuroelectric activity from within microchannels [7]- [11]. Microchannels ranging from 2.5 to 20 m wide are examined to see if this has an influence on the ability to counter fasciculation and to see if supporting evidence can be found for hypothesized mechanisms of initiating separated growth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fabrication costs can be reduced to a minimum by simplifying fabrication procedures [74], materials [75] and increasing quantities of the devices produced.…”
Section: Microelectrode Arrays (Meas)mentioning
confidence: 99%